Tensile Deformation Behaviour of Dual Phase Steel Under Various Processing Conditions: A Review - Kosaraju, Satyanarayana; Sammeta, Vamshi; A K, Singh (International Journal of Integrated Engineering, 2024)
Present paper presents a state-of-the-art overview of the dual phase (DP) steels which are widely used materials in the manufacturing of automotive parts/components. These materials have high strength-to-weight ratio and optimum ductility which make them outstanding characteristics compared to those of the other conventional steels. The uniaxial tensile deformation behaviour of DP steels is presented which are tested under various heat treatment conditions at ambient temperature and elevated temperatures. Mechanical properties have been evaluated under static and dynamic conditions as well as different strain rates. The different works reported by the researchers are presented as a consolidated summary and compared various material properties such as yield strength (YS), ultimate tensile strength (UTS) and total elongation